Implementation of innovative tools for socio-economic protection of operators and consumers (Economics and region, 2023)
This article explores the tools for socio-economic protection in the online gambling industry. It delves into various aspects of this field, including honest business practices, access to information, transaction security, data privacy, supply chain product safety, dispute resolution mechanisms, and combating fraudulent activities. The main focus is to enhance trust and safeguard the interests of both operators and consumers within the online gambling sector. The primary theme of the article centers around creating a framework that fosters fair and secure online gambling practices. It delves into the prevalent issues such as deceptive practices, website cloning, dishonest pricing strategies, and the reliability of user reviews and ratings. The article aims to address these concerns and provide recommendations for a more transparent and trustworthy online gambling environment. The overarching goal of this research is to elevate the level of trust among players in online gambling and prevent fraudulent activities within the industry. By examining high-level principles, the article lays the foundation for ethical business conduct, accessibility to crucial information, and effective transaction verification. The article's comprehensive results include a set of guidelines and recommendations for implementing socio-economic protection tools. These tools aim to improve the gaming experience and protect consumers' rights in the online gambling sphere. By introducing these measures, the industry can promote a fair and reliable gambling environment where operators and players alike adhere to ethical and legal standards. Furthermore, this article sheds light on the critical role of digital comparison tools in empowering consumers with accurate information and ensuring the integrity of online gambling platforms. Overall, this research serves as a valuable resource for stakeholders in the online gambling industry, offering insights and strategies to create a safer and more trustworthy gaming ecosystem. It underscores the importance of honest business practices, transparency, and consumer protection, ultimately contributing to a healthier and more sustainable online gambling landscape.
Keywords: gambling; online gaming; socioeconomic protection; ratings and reviews; fair practices